Bilateral Acoustic Neuroma with underlying Neurofibromatosis Type 2: A Therapeutic Challenge - Mohamad, Irfan; Alias, Azila; Daud, Mohd Khairi M (Bangladesh Journal of Medical Science, 2012)
The presence of bilateral acoustic neuroma may require modification of the usual therapeutic protocol. Preservation of hearing and total removal of the tumour is much more difficult than in sporadic unilateral lesion. This case illustrates the management of a girl with bilateral acoustic neuroma with underlying neurofibromatosis type 2. DOI: http://dx.doi.org/10.3329/bjms.v11i4.12609 Bangladesh Journal of Medical Science Vol. 11 No. 04 Oct12